Peningkatan Kapasitas Guru melalui Pelatihan Soal HOTS dan Asesmen Diagnostik dalam Pembelajaran Berdiferensiasi - Pranti Sayekti; Swastika Dhesti Anggriani (LPkM Universitas Bakrie, 2026)
The phenomenon of teachers’ limited ability to design assessment instruments based on higher-order thinking skills has become a major challenge at SMA Muhammadiyah 1 Malang. Initial surveys and focus group discussions with 20 teachers showed that most still relied on lower-order thinking questions and had not yet utilized diagnostic assessments to support differentiated instruction. This condition contributes to students’ low abilities in critical thinking and contextual problem-solving, despite both being essential competencies in the twenty-first century. To address this issue, the implementation team developed a teacher capacity-building program through integrated training on Higher Order Thinking Skills (HOTS) and diagnostic assessment. The three-month program used a participatory approach, involving teachers in needs identification, assessment storyboard development, and visual design for differentiated learning, workshops, and classroom implementation mentoring. Activities included training on HOTS-based item construction, assessment simulations using Cognitive Diagnostic Assessment (CDA), and the application of Differentiated Instruction (DI) with tiered tasks aligned with students’ learning profiles. The program results showed significant improvement in teachers’ ability to design HOTS instruments and diagnostic assessments. Key outputs included a HOTS item bank, diagnostic assessment storyboard templates, and cross-subject differentiated learning designs. The program also fostered the development of a reflective practice–based teacher mentoring model, which was replicated through the school’s Professional Learning Community (PLC) as a platform for sustained collaboration and innovation at the regional level.